The pattern of admission and their related outcomes in NICU of a tertiary care teaching hospital, Udaipur, Rajasthan, India - Dr. Ujjwal Mittal; Dr. Vivek Parasher; Dr. Rahul Khatri; Dr. Samarth Yadav; Dr. Sayan Das (Pediatric Review: International Journal of Pediatric Research, 2021)
Introduction: To achieve MDG4 (Millennium Developmental Goals-4), a substantial reduction in early neonatal deaths will be required. The first steps in improving early neonatal survival are to document the number and rate of deaths and identify their common causes. As per the National Family Health Survey-3 report, the current neonatal mortality rate (NMR) in India is 39 per 1000 live births, neonatal deaths account for nearly 77% of all infant deaths (57/1000) and nearly half of under-ﬁve child deaths (74/1000). This study was undertaken to study the disease pattern and outcome of neonates admitted to the neonatal intensive care unit (NICU) of a tertiary care teaching hospital located in Udaipur, Rajasthan.Material and methods: The age, sex, gestational age, and morbidity and mortality profile of all NICU admissions in 5 years was determined and the difference between Inborn (those born in the Teaching Hospital) and Out born was calculated. Morbidity risk factors to reduce NMR in Udaipur were determined.Results: A total of 2648 neonates were admitted to NICU during the study period, out of which none were excluded from the study. The ratio of Male to Female admitted was 1.30:1. The major causes of morbidity were Meconium Aspiration Syndrome (16.16%), Respiratory Distress Syndrome(10.12%), Cong. Heart Defects(8.76%), Neonatal Sepsis(4.83%) and Hypoxic-Ischemic Encephalopathy(5.66%). In this study, the overall mortality rate was 9.96%. Most of the Deaths were due to MAS(25.75%), RDS(15.90%), Neonatal Sepsis(10.22%), and HIE(12.87%). Neonates with birth weight <1000g had poor outcomes compared to neonates with birth weight >2500g.Conclusion: This study identified Prematurity, Extremely low birth weight, MAS, and Neonatal Sepsis as major causes of Morbidity and MAS, RDS as the major contributors to neonatal mortality. Improving antenatal care, maternal health, and timely referral of high-risk cases to tertiary care hospitals will help to improve neonatal outcomes.